Managing quality - Hamson, Ned; Zuckerman, Amy (ExpressExec operations, 2002)
Fast track route to mastering quality management. Covers the key areas of quality management, from understanding the vital connections between customers and ISO 9000-2000 to the key steps to develop a practical, performance enhancing quality management process